Current Management Strategies in Oral Submucous Fibrosis: Life Sciences- Oral Medicine - D. Badki, Dr. Simran; K. Lohe, Dr. Vidya; Bhowate, Dr. Rahul; Dangore, Dr. Suwarna; Meshram, Dr. Mrunal; Bhargava, Dr.Pragati (International Journal of Life Science and Pharma Research, 2023)
Oral sub-mucous fibrosis is a premalignant condition recently recognized as "areca nut-induced oral fibrosis." It is "achronic disease which is irreversible, affecting oral and systemic health of patients." However, Areca nut or betel nut is the primaryetiologic reason for Oral Submucous fibrosis (OSMF); other factors like excess chilies intake, nutritional deficiencies, andimmunological factors are also considered causative agents for the disease. It causes inflammation and fibrosis of the submucosaltissues causing trismus and rigid oral mucosa. The treatment for this disorder includes numerous conservative, medicinal, andsurgical management; however, no treatment modality has been proven to be a standard treatment option. Herbal modalities areseen to be more effective in OSMF treatment. Unfortunately, the literature on the management of OSMF cannot do justice to allthe treatment modalities at one stop. The new trends and treatment modalities for OSMF keep adding up from time to time, andyet formulating the perfect treatment protocol for OSMF management is still challenging for dental clinicians due to themultifactorial etiology, complexity of the disease, and changing trends in treatment. The present review aimed to enlighten cliniciansabout the current disease scenario and tried to include all the latest treatment modalities. The objectives are to review and assessthe existing situation of this disease with a brief on the efficacy of different available treatment modalities used to help dentalphysicians formulate a treatment protocol with knowing the proper effects, advantages, and disadvantages of each modality andenlightening the potential future treatment options for OSMF.